MOLECULAR SCREENING OF COMPLEX VERTEBRAL MALFORMATION AND CITRULLINEMIA CARRIERS IN PAKISTANI NILI-RAVI BUFFALO (BUBALUS BUBALIS) BREEDING BULLS - K. Zahra; M. Imran; M. Y. Zahoor; K. Ashraf; K. H. Jaffry; A. Nadeem; I. Rashid; M. Younas; M. Akhtar; W. Shehzad (Journal of Animal and Plant Sciences, 2020)
Inherited disorders have serious implications for cattle production and breeding programs. Structural or physiological abnormalities and neonate lethality have negative impacts on breeding populations. Complex vertebral malformation (CVM) and bovine citrullinemia (BC) are heritable congenital syndromes having autosomal recessive basis among cattle breeds worldwide. CVM affected malformed foetuses either get aborted or have evident skeletal deformities upon birth and die during early postnatal period. CVM is caused by a missense substitution (G→T) in uridine diphosphate N-acetylglucosamine transporter encoded by SLC35A3 gene (at position 559). Citrullinemia is a heritable metabolic disorder of urea cycle enzyme argininosuccinate synthetase deficiency which occurs due to a transition (C→T) within exon 5 (codon 86) of ASS1 gene with neurological complications during first week after birth. Both of these fatal disorders have been reported from all over the world in Bos taurus but there is a lack of literature on buffaloes. The present study was carried out to detect CVM and BC carriers among the Pakistani indigenous trans-husbandry water buffalo breed, Nili-Ravi (Bubalus bubalis). In this study, the genetic screening for the target point mutations was carried out using healthy elite buffalo bulls (n=152). Genomic DNA was extracted from the blood and SLC35A3 gene target sequence (281 bp) and ASS1gene target sequence(505 bp) were amplified using PCR. Amplified PCR products were visualized by agarose gel electrophoresis and Sanger sequencing was performed. No carriers were detected among the study sample, however, a novel transversion (c.250C>A) was detected in amplified ASS1 gene fragment. Although, findings of this study confirmed absence of CVM and citrullinemia carriers among the Nili-Ravi buffalo bulls but the presence of carrier animals cannot be ruled out in studies involving larger sample sizes. This genetic screening was carried out for the first time in Pakistani buffaloes which can be used in genetic screening of CVM or BC carrier animals in the future. Further research is recommended in order to enhance the existing data regarding CVM and BC carriers among Bubalus bubalis.
Keywords: Complex vertebral malformation; citrullinemia; Nili-Ravi buffaloes